Gripping adhesive principles in the design of effectors - Marcel Horák; Michal Starý; Ondřej Matúšek; František Novotný (SN Applied Sciences, 2022)
Abstract This article presents a basic study of knowledge in the research and development of specific gripping elements based on the principle of adhesion. It summarizes the use of materials with a high degree of surface adhesion in the design of gripping elements usable in industry to provide stable gripping of objects during automatic manipulation. The principle of a combined element proposed by the authors, where the gripping force is derived through both vacuum and adhesion, is presented. The conditions of operation in an active or completely passive mode without the need to connect an energy source are discussed in detail. In the active mode, a significant increase in gripping forces is demonstrated compared to standard vacuum elements, which has a positive effect on the amounts of compressed air consumed and the level of grip safety in production processes. To ensure the optimal function of the adhesive gripping elements, the design of a specifically designed fluid position compensator and an active system for disturbing the adhesive gripping forces is presented. The functionality of the designed element is demonstrated through several laboratory tests under various conditions, and the results clearly confirm an increase in gripping forces in the axial and in particular the radial direction of the load. The research includes the design of a computer model of deformation-adhesive contact, respecting the time dependence of the deformation of the adhesive layer and the gradual loss of contact with the object. Article highlights: o Experimental study presents use of PU materials in adhesive and combined gripping elements. o Adhesive contact theory is applied for a numerical simulation and prepared computer model is subsequently verified. o Authors present new proprietary solution of gripping element applicable in industrial robotics.